(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this Research, proposed algorithm namely Right Maximum Minimum Allotment method is applied to find the optimal feasible solution to reduce the cost from the basic feasible solution for transportation problems. The proposed algorithm is a unique way to reach the feasible (or) may be optimal (for some extant) solution without disturbance of degeneracy condition